2006
DOI: 10.1111/j.1460-9592.2005.01826.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery in the pediatric patient post Fontan procedure

Abstract: We present two case reports describing laparoscopic surgery in patients who have undergone previous Fontan surgery and discuss the theoretical implications of laparoscopic surgery in these patients. A brief discussion of the late complications of Fontan surgery is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Increased intraabdominal pressure from insufflation and elevated arterial carbon dioxide tension in laparoscopic surgery will increase PVR and decrease cardiac output. Successful laparoscopic surgery has been described in functional Fontan [40,41]. Limiting insufflation pressure to 10-12 mmHg seems to reduce the adverse effects of laparoscopy in these case reports.…”
Section: Anesthetic Managementmentioning
confidence: 95%
See 1 more Smart Citation
“…Increased intraabdominal pressure from insufflation and elevated arterial carbon dioxide tension in laparoscopic surgery will increase PVR and decrease cardiac output. Successful laparoscopic surgery has been described in functional Fontan [40,41]. Limiting insufflation pressure to 10-12 mmHg seems to reduce the adverse effects of laparoscopy in these case reports.…”
Section: Anesthetic Managementmentioning
confidence: 95%
“…Various case reports have been reported with their successful anesthetic management [36][37][38][39][40][41][42][43][44][45][46], including a case for failing Fontan [47].…”
Section: Post-fontan Patientsmentioning
confidence: 99%
“…Thromboembolic complications are also a well-recognized source of morbidity, given the nonpulsatile and sometimes diminished flow through Fontan pathways [20]. Incidence ranges from 3% to 20% [21][22][23]. While the routine use of anticoagulation remains controversial, a recent outcome study found the absence of aspirin or warfarin therapy to be powerful independent predictors of mortality from thromboembolism [24].…”
Section: Discussionmentioning
confidence: 98%
“…The procedure usually corrects cyanosis and imparts a good quality of life, but it has limitations that affect anesthetic management. 1 Patients with a single ventricle and residual right-to-left communication, e.g., Glenn shunts, receive blood from the venous side of the heart; however, in patients with a completed Fontan palliation, ventricular filling is dependent entirely on pulmonary venous return (Figure). These patients require an elevated central venous pressure (CVP), and a low-normal pulmonary and systemic vascular resistance to maintain pulmonary blood flow and cardiac output.…”
Section: Résumémentioning
confidence: 98%